Effect of growth hormone treatment on children with idiopathic short stature (ISS), idiopathic growth hormone deficiency (IGHD), small for gestational age (SGA) and Turner syndrome (TS) in a tertiary care center - Al Shaikh, Adnan; Daftardar, Hadeer; Alghamdi, Abdul Aziz; Jamjoom, Majd; Awidah, Saniah; Ahmed, Mohamed E; Soliman, Ashraf T (Acta Biomedica Atenei Parmensis, 2020)
Objectives: To assess the long-term effect of growth hormone (GH) therapy in a large cohort of short children with different etiologies. Patients and Methods: We evaluated retrospectively the anthropometric data of 252 short children [height SDS <-2: 154 children with growth hormone deficiency (GHD), 63 with idiopathic short stature (ISS), 26 with SGA, and 9 with Turner syndrome (TS)] who were treated, in our center, with GH between 1-2007 and 1-2018. Before and during recombinamt growth-hormone (recGH) treatment, auxological parameters including height (Ht), weight (Wt), Ht - Z score (HtSDS), body mass index (BMI) and BMISDS were recorded every 6 months; bone age (BA) was assessed every 12 months. Results: At the end of first year of rhGH therapy and after an average of 3 years treatment all groups of short children had significant increase in HtSDS, which was higher in GHD compared to other groups. Children with GHD, SGA, ISS and TS increased their HtSDS by an average of 2.2, 1.46, 0.6 and 0.99 SD, respectively at the end of follow up period (for all groups, p: <0.001). The bone age/chronological age (BA/CA) ratio did not differ significantly among ISS, GHD and SGA groups after GH therapy. The HtSDS gain was higher in children with GHD compared to other ISS, SGA and TS groups (p:< 0.01; p: 0.015 and p: 0.029, respectively). HtSDS improvement occurred during the first 3 years of rhGH therapy. The BMISDS increased significantly in children with GHD, after 3 years of rhGH therapy (p: < 0.001). After rhGH treatment, the BMISDS decreased significantly in children with ISS and SGA (p: < 0.01 and < 0.001, respectively) but did not change in children with TS (p: 0.199). Conclusions: Children with GHD, SGA, ISS and TS exhibited significant increases in HtSDS when treated with rhGH for 3 years. The HtSDS gain was higher in children with GHD compared to other groups.